2021
DOI: 10.1177/1759720x211002582
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors that drives arthrocentesis for suspected septic joint

Abstract: Introduction: This study aims to develop a simple diagnostic criterion that could be used to justify arthrocentesis in adults with suspected septic arthritis. Our hypothesis is that no single factor will be predictive for a decision to aspirate a questionable septic joint. Methods: A prospective observational cohort study was performed at a Level 1 Trauma institution including all patients over the age of 18 years referred to Orthopaedics through the Emergency Department or inpatient orthopaedic consultations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…Although positive synovial fluid cultures are useful for the diagnosis of septic arthritis, they may be negative in patients already taking antibiotics before the culture or in infections with fastidious organisms [14,15] . Synovial fluid cultures were positive in 75.67% of our patients, which considered it a sensitive method to diagnose septic arthritis, and this is compatible with other studies [1,3,5,16,17] .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although positive synovial fluid cultures are useful for the diagnosis of septic arthritis, they may be negative in patients already taking antibiotics before the culture or in infections with fastidious organisms [14,15] . Synovial fluid cultures were positive in 75.67% of our patients, which considered it a sensitive method to diagnose septic arthritis, and this is compatible with other studies [1,3,5,16,17] .…”
Section: Discussionsupporting
confidence: 91%
“…The sensitivity of WBC levels greater than 50 000/l in adults with septic arthritis ranges from 50 to 70% [1,3] . In our study, the elevated white cell count was around 11.323.6103/l, which is not very high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the gold standard test for the diagnosis of knee SA is joint aspirate analysis, with synovial WBC counts >50,000 μL. 40 Amongst the 12 performed arthrocenteses in our study, synovial leucocytic counts (as summarized in Table 4 ) demonstrated marked elevation compared to previous authors. 15 Notably, a previous observational study, which included 24 infected and 14 uninfected patients, underlined that at a cutoff value of 40,000 WBCs/mL; diagnosis of postoperative SA could be achieved with 100% specificity.…”
Section: Discussioncontrasting
confidence: 41%